2021
DOI: 10.1186/s13048-021-00914-w
|View full text |Cite|
|
Sign up to set email alerts
|

Polycystic ovary rat model exposure to 150 kHz intermediate frequency: hypothalamic-pituitary-ovarian axis at the receptor, cellular, tissue, and hormone levels

Abstract: Introduction The hypothalamic-pituitary-ovarian (HPO) axis is the principal regulator of the reproductive system. The neurons in the arcuate nucleus of the hypothalamus signal the basophilic cells of the anterior pituitary to release luteinizing hormone (LH) and follicle stimulating hormone (FSH), which bind to the granulosa and theca cells of a follicle in the ovary to promote healthy follicular development. Disruption of this process at any time can lead to polycystic ovaries and, if left unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Rats were randomly divided into two groups (control and EMR group) created with Microsoft Excel using = RAND (), with 10 animals per group. The EMR group was continuously irradiated with 150 kHz EMR from an EMR generation system for two months (except for approximately one hour per week needed for cage changes) [23,24]. The control group was not irradiated with EMR from the device.…”
Section: Animal Care and Husbandrymentioning
confidence: 99%
See 2 more Smart Citations
“…Rats were randomly divided into two groups (control and EMR group) created with Microsoft Excel using = RAND (), with 10 animals per group. The EMR group was continuously irradiated with 150 kHz EMR from an EMR generation system for two months (except for approximately one hour per week needed for cage changes) [23,24]. The control group was not irradiated with EMR from the device.…”
Section: Animal Care and Husbandrymentioning
confidence: 99%
“…In contrast, numerous epidemiological, in vivo, and in vitro studies confirm the safety of the IF [18][19][20][21]. In addition, recent innovative research has demonstrated the efficacy of this field (100 kHz-300 kHz) in disrupting mitosis in cancer cells [22] and in slowing the development of follicular cysts in polycystic ovaries (PCOs) [23,24]. However, these studies are controversial and do not lead to a clear conclusion because there are many differences in exposure duration, frequency, orientation, modulation, and power density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal frequency for the antimitotic effect varies by cancer type and can be adjusted for maximum anti-cancer effect. In the preclinical setting, 150-kHz TTFs are effective in treating pancreatic cancer, non-small cell lung carcinoma (NSCLC), brain metastases from NSCLC, and mesothelioma when combined with chemotherapy [ 16 ] and in reducing the number of cysts in polycystic ovary disease in rats [ 17 , 18 ]. Since mammalian testicular germ cells proliferate clonally via mitotic rounds before differentiating into mature spermatozoa, the effect of IF on any reproductive risks in this TTF range (100 kHz–300 kHz) needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The original article [ 1 ] contains errors in Figs. 3 and 7 which occurred during the compilation of the images into figures.…”
mentioning
confidence: 99%